2002
DOI: 10.1152/ajpregu.00086.2002
|View full text |Cite
|
Sign up to set email alerts
|

Renal endothelin in chronic angiotensin II hypertension

Abstract: To determine the influence of chronic ANG II infusion on urinary, plasma, and renal tissue levels of immunoreactive endothelin (ET), ANG II (65 ng/min) or saline vehicle was delivered via osmotic minipump in male Sprague-Dawley rats given either a high-salt diet (10% NaCl) or normal-salt diet (0.8% NaCl). High-salt diet alone caused a slight but not statistically significant increase (7 Ϯ 1%) in mean arterial pressure (MAP). MAP was significantly increased in ANG II-infused rats (41 Ϯ 10%), and the increase in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
112
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 103 publications
(121 citation statements)
references
References 18 publications
8
112
1
Order By: Relevance
“…25,26 In the present study, the combination of a high-salt diet and angiotensin II infusion resulted in a greater increase in systolic blood pressure, which confirms salt sensitivity of angiotensin II-induced hypertension reported previously using radiotelemetry to measure arterial blood pressure. 27 It is generally accepted that excess dietary salt intake differentially modulates the activity of CYP450 enzymes in kidney. Precisely how increased circulating angiotensin II levels change the regulatory effect of a highsalt diet on CYP450 enzymes remains unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…25,26 In the present study, the combination of a high-salt diet and angiotensin II infusion resulted in a greater increase in systolic blood pressure, which confirms salt sensitivity of angiotensin II-induced hypertension reported previously using radiotelemetry to measure arterial blood pressure. 27 It is generally accepted that excess dietary salt intake differentially modulates the activity of CYP450 enzymes in kidney. Precisely how increased circulating angiotensin II levels change the regulatory effect of a highsalt diet on CYP450 enzymes remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is in agreement with previous studies demonstrating impaired NO/cyclic guanosine monophosphate signaling in spontaneously hypertensive rats fed a high-salt diet and the increase of the NO synthase inactivator N G -N G -dimethyl-arginine in the kidney of angiotensin II-infused rats fed a high-salt diet. 27 Clearly, further investigation is required to delineate the role of EETs in the depressed vascular response to acetylcholine and sodium nitroprusside that develops in angiotensin II salt-sensitive hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have suggested a prominent role of ET in the control of renal plasma flow and renal sodium excretion and, thereby, the renal control mechanisms of arterial pressure. 13,16,17,25 However, the role of ET in the vascular control mechanisms of arterial pressure has not been clearly established.ET is one of the most potent vasoconstrictors described. 26…”
mentioning
confidence: 99%
“…9 -12 Although the mechanisms of salt-sensitive hypertension have not been clearly identified, several studies point to a possible role of endothelin (ET). 7,[13][14][15][16][17] ET has been shown to interact with specific ET A and ET B receptors in tissues involved in the regulation of arterial pressure, particularly the kidney and the vasculature. 18 -24 Studies with specific ET A and ET B antagonists have suggested a possible role of ET as a mediator of angiotensin II-induced hypertension in rats, particularly during HS.…”
mentioning
confidence: 99%
See 1 more Smart Citation